Seismically invisible fault zones: Laboratory insights into imaging faults in anisotropic rocks. Issue 16 (16th August 2017) - Kelly, C. M.; Faulkner, D. R.; Rietbrock, A.
Abstract: Phyllosilicate‐rich rocks which commonly occur within fault zones cause seismic velocity anisotropy. However, anisotropy is not always taken into account in seismic imaging and the extent of the anisotropy is often unknown. Laboratory measurements of the velocity anisotropy of fault zone rocks and gouge from the Carboneras fault zone in SE Spain indicate 10–15% velocity anisotropy in the gouge and 35–50% anisotropy in the mica‐schist protolith. Greater differences in velocity are observed between the fast and slow directions in the mica‐schist rock than between the gouge and the slow direction of the rock. This implies that the orientation of the anisotropy with respect to the fault is key in imaging the fault seismically. For example, for fault‐parallel anisotropy, a significantly greater velocity contrast between fault gouge and rock will occur along the fault than across it, highlighting the importance of considering the foliation orientation in design of seismic experiments. Key Points: Ultrasonic velocities are measured in the laboratory to quantify anisotropy due to rock fabric in phyllosilicate‐rich Carboneras fault Compressional and shear wave velocities show anisotropy of 10–15% in the Carboneras fault gouge and 35–50% in the mica‐schist protolith The degree and orientation of seismic anisotropy with respect to a fault may be a key consideration in seismic imaging of the fault